Al-I'jāz al-Ilmī 'an Khalqi aż-żubab fī Al-Qur'an 'inda Ṭanṭāwī Jauharī : الإعجاز العلمي عن خلق الذباب في القرآن عند طنطاوي جوهري - Rochmad, Rochmad; Fitriani, Fitriani; Sylvia, Niken; Shopia, Averosian; Dyah, Yusrina (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2023)
There are so many scientific signs in the Qur’an. Including scientific cues in verses that talk about insects. One of the insects recorded in the Qur’an is a fly, even the Qur’an directly relates the creation of this fly to a theological problem. This paper seeks to explore scientific wisdom in the verse regarding the creation of flies which are often underestimated by humans because of their existence which is considered not to bring benefits but on the contrary as a source of disease according to Thantawi Jauhari. Research using the descriptive approach has several conclusions, including that Thantawi Jauhari explained the unique design of the fly's limbs, especially the fly's eyes and wings. Flies also help reduce airborne diseases and fungi that can cause more severe illnesses in humans. In addition, Thantawi also tried to explain the wisdom of the creation of flies. The verse about the design of flies shows how weak humans are before God, especially statues worshippers.